2009
DOI: 10.1155/2009/649654
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Antimicrobial Activity of s‐Triazine Hydrazones of 7‐Hydroxy Coumarin and their Metal Complexes

Abstract: Metal complexes of 7-hydroxy coumarin hydrazone ofs-triazine derivatives derived from 7-hydroxy-8-aceto-N-(4',6’-dichloro-1',3',5'-s-triazine) coumarin hydrazone and transition metals have been synthesized and screened for their antibacterial, antifungal and antiseptic activity. The geometry of the complexes has been proposed. The ligand system co-ordinates with the metal ion in a bidentate manner through the nitrogen atom of hydrazone group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 4 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…They have been used as an intermediate for the preparation of heterocycles displaying useful activities [ 8 , 9 ]. Recently Jani et al has reported the synthesis and antimicrobial activities of complexes prepared using ligands containing triazine and hydrazone functionalities [ 10 ]. The vast range of pharmacological applications of these classes of compounds encouraged us to synthesize compounds containing both triazine and hydrazone moieties.…”
Section: Introductionmentioning
confidence: 99%
“…They have been used as an intermediate for the preparation of heterocycles displaying useful activities [ 8 , 9 ]. Recently Jani et al has reported the synthesis and antimicrobial activities of complexes prepared using ligands containing triazine and hydrazone functionalities [ 10 ]. The vast range of pharmacological applications of these classes of compounds encouraged us to synthesize compounds containing both triazine and hydrazone moieties.…”
Section: Introductionmentioning
confidence: 99%
“…Delivering the current of 150 mA subjected to electroshock to the animals through the corneal electrodes for a period of 0.2 seconds. The animal was observed convulsive responses for 30 min [33]. Minimal Neurotoxicity.…”
Section: Primary Evaluationmentioning
confidence: 99%
“…Besides, they found in different oils as ''lavender oil, cinnamon bark, oil and cassia oil'' [4]. Moreover, coumarin derivatives have changed uses such as '' optical brightening agents, laser dyes, cosmetic industry agrochemical industries and food additives'' [5][6][7]. Furthermore, Coumarin derivatives have important biological activity as antibacterial, antifungal, anti-oxidant, anti-allergic, antiinflammatory, anti-thrombotic, hepatoprotective, anti-viral, anticarcinogenic activities [8][9][10].…”
Section: Introductionmentioning
confidence: 99%